Strategic Management in Developing Globally Competitive Islamic Educational Institutions (PT. LARPA JAYA PUBLISHER, 2024)
This study explores the strategic management approach in developing globally competitive Islamic educational institutions. The research aims to analyze how effective strategic planning, implementation, and evaluation can enhance the quality, sustainability, and competitiveness of Islamic education in the global era. Using a literature review method covering studies published between 2010 and 2023, the analysis focuses on leadership, curriculum innovation, human resource development, technological integration, and global collaboration. The results reveal that applying strategic management principles enables Islamic educational institutions to balance modern educational demands with Islamic values, fostering institutions that are adaptive, innovative, and competitive. Leadership with a global vision, technology-based learning strategies, and collaboration with international partners are identified as key success factors. Furthermore, the integration of Islamic ethics in management practices strengthens institutional identity while promoting global engagement. In conclusion, strategic management is not only essential for improving institutional performance but also for ensuring the holistic development of Islamic education that upholds faith-based values in the global context.